2018
DOI: 10.3390/molecules23092180
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bacterial Adhesion Activity of Tropical Microalgae Extracts

Abstract: The evolution of regulations concerning biocidal products aimed towards an increased protection of the environment (e.g., EU Regulation No 528/2012) requires the development of new non-toxic anti-fouling (AF) systems. As the marine environment is an important source of inspiration, such AF systems inhibiting the adhesion of organisms without any toxicity could be based on molecules of natural origin. In this context, the antibiofilm potential of tropical microalgal extracts was investigated. The tropics are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Methanol extraction is an established and well-reported method to isolate active antimicrobial components from microalgae ( Patil and Kaliwal, 2019 , Zea-Obando et al, 2018 ). Table 3 shows the obtained ME from UKM8 and UKM9 were effective against a broader spectrum of Gram-positive and Gram-negative bacteria, which could be considered as promising antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Methanol extraction is an established and well-reported method to isolate active antimicrobial components from microalgae ( Patil and Kaliwal, 2019 , Zea-Obando et al, 2018 ). Table 3 shows the obtained ME from UKM8 and UKM9 were effective against a broader spectrum of Gram-positive and Gram-negative bacteria, which could be considered as promising antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, the Chlorophyta phylum is known for its ability to synthesize a variety of bioactive compounds such as lipids and derivative polyunsaturated fatty acids (PUFAs). Specifically, two PUFAs, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), have demonstrated to exhibit antibacterial and antibiofilm properties [68,69]. However, in this study, their presence was not evident.…”
Section: Antibiofilm Activity Of Compounds Isolated From Microalgaementioning
confidence: 60%
“…The methanolic extract is a well-established and reported method to isolate active antimicrobial components from microalgae [37,38]. In another study, methanol was found to be the best organic solvent to obtain bioactive compounds from Dunaliella sp.…”
Section: Discussionmentioning
confidence: 99%